The Relationship between Healthcare Expenditure and Disposable Personal Income in the US States: A Fractional Integration and Cointegration Analysis - Guglielmo Maria Caporale; Juncal Cunado; Luis A. Gil-Alana; Rangan Gupta (Center for Economic Studies and ifo Institute (CESifo), 2015)
This study examines the relationship between healthcare expenditure and disposable income in the 50 US states over the period 1966-2009 using fractional integration and cointegration techniques. The degree of integration and non-linearity of both series are found to vary considerably across states, whilst the fractional cointegration analysis suggests that a long-run relationship exists between them in only 11 out of the 50 US states. The estimated long-run income elasticity of healthcare expenditure suggests that health care is a luxury good in these states. By contrast, the short-run elasticity obtained from the regressions in first differences is in the range (0,1) for most US states, which suggests that health care is a necessity good instead. The implications of these results for health policy are also discussed.
Keywords: C22; C32; H51; I18; 330; healthcare expenditure; income elasticity; US states; fractional integration; fractional cointegration